2016
DOI: 10.1016/j.eatbeh.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of negative reinforcement eating expectancies in the relation between experiential avoidance and disinhibition

Abstract: Objectives Eating-related disinhibition (i.e. a tendency to overeat in response to various stimuli) is associated with weight gain and poorer long-term weight loss success. Theoretically, experiential avoidance (i.e., the desire or attempts to avoid uncomfortable internal experiences), may predispose individuals to developing negative reinforcement eating expectancies (i.e., the belief that eating will help to mitigate distress), which in turn promote disinhibition. Such relationships are consistent with an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…Furthermore, to be determined and careful (characteristics of those temperaments) can contribute to not adopt frequent eating-compensatory behaviors, or do it less frequently than a cyclothymic individual for example. Contrasting to this, previous researches found association between eating-compensatory behaviors and different temperaments, especially irritable (Garner et al, 1990; Fassino et al, 2001), avoidant (Baños et al, 2014; Schaumberg et al, 2016) and obsessive types (Kleifield et al, 1994). This difference can be explained by the focus of studies which were based mostly on anorexic (Baños et al, 2014) and bulimic patients (Garner et al, 1990), instead of the general population, such as this sample.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, to be determined and careful (characteristics of those temperaments) can contribute to not adopt frequent eating-compensatory behaviors, or do it less frequently than a cyclothymic individual for example. Contrasting to this, previous researches found association between eating-compensatory behaviors and different temperaments, especially irritable (Garner et al, 1990; Fassino et al, 2001), avoidant (Baños et al, 2014; Schaumberg et al, 2016) and obsessive types (Kleifield et al, 1994). This difference can be explained by the focus of studies which were based mostly on anorexic (Baños et al, 2014) and bulimic patients (Garner et al, 1990), instead of the general population, such as this sample.…”
Section: Discussionmentioning
confidence: 71%
“…This difference can be explained by the focus of studies which were based mostly on anorexic (Baños et al, 2014) and bulimic patients (Garner et al, 1990), instead of the general population, such as this sample. Moreover, some studies focused in specific population such as obese (Baños et al, 2014) and overweight (Schaumberg et al, 2016), whereas most participants in this study have normal body mass index. Importantly, in our sample the diagnosis of eating-compensatory behaviors was based on the self-report measures of participants.…”
Section: Discussionmentioning
confidence: 74%
“…The high levels of experiential avoidance reported amongst individuals across samples who reported high ID suggest that they may be using food as an unhealthy coping strategy to try to change or influence their thoughts, feelings or bodily sensations. Previous research has demonstrated that the relationship between experiential avoidance and disinhibition (not distinguished by internal vs. external) in individuals who are overweight/obese was accounted for by expectations that eating will alleviate distress . Acceptance‐based interventions attempt to undermine such coping strategies by teaching individuals how to be more mindful and open, allowing for more flexible behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of expectancies has not been assessed in LOCE as an independent construct, prior literature implicates expectancies eating will alleviate negative affect (NA reduction expectancies) in related eating pathology. NA reduction expectancies are higher in individuals with binge pathology (Boerner et al, 2004;Hayaki, 2009;Hohlstein et al, 1998;Schaumberg et al, 2016;Simmons et al, 2002) and are associated with greater binge eating frequency (De Young et al, 2014;Fischer & Smith, 2008) as well as endorsement of symptoms (Hayaki, 2009). In addition, NA reduction expectancies longitudinally predict future binge eating symptom onset (Smith et al, 2007) and have been found to be correlated with greater emotion regulation difficulties (Hayaki & Free, 2016;Kauffman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%